Preparation method and application of PC-SP-MCN double-layer Janus composite membrane for cooperatively driving interface evaporation and photocatalysis by solar energy
Through the PC-SP-MCN double-layer Janus composite film with coordinated solar-driven interface evaporation and photocatalysis, the problems of low evaporation rate, poor salt resistance and insufficient anti-biological pollution performance in the prior art are solved, and efficient seawater desalination and wastewater are achieved Purification.
Patent Information
- Application Number
- CN202411450358.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The prior art has problems such as low evaporation rate, poor salt resistance and insufficient anti-biological pollution performance in the application of solar photothermal materials, making it difficult to effectively purify the salt-containing and biologically contaminated wastewater.
A PC-SP-MCN double-layer Janus composite film with synergistic solar-driven interface evaporation and photocatalysis was used to prepare a film with excellent salt resistance and anti-biological pollution properties through the combination of SiO2-PIL and MXene/g-C3N4.
It realizes efficient solar-driven interface evaporation and photocatalysis, significantly improves the efficiency of seawater desalination and wastewater purification, and has good salt and pollution resistance.
Smart Images

Figure CN119455679A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a preparation method and application of a PC-SP-MCN double-layer Janus composite film driven by solar energy for interfacial evaporation and photocatalysis. Background Art
[0002] In order to cope with the major problem of limited freshwater supply in the 21st century, various methods have been created and implemented to regenerate freshwater, including technologies such as reverse osmosis and thermal distillation. At present, in order to efficiently utilize solar energy, photovoltaics, photocatalysis, SDIE and other clean and promising sustainable energy sources have been created. One of the most effective methods for water purification or desalination is SDIE, which also does not require a large amount of infrastructure and reduces energy consumption. However, the limited evaporation surface area and salt crystallization problems lead to a reduced evaporation rate, which greatly hinders the practical application of solar thermal materials. In addition, the rapid development of economy and industry has created an urgent need for multifunctional purification. The biggest hidden danger is that the direct discharge of biological pollutants and organic solvents containing dyes poses a significant risk to the environment and human health. Traditional technologies such as filtration and organic solvent nanofiltration (OSN) are pressure-driven separation processes that inevitably consume a lot of energy. Therefore, it is urgent to develop a new type of photothermal material that exhibits excellent salt tolerance and effective anti-biofouling performance in the SDIE process for continuous water purification, and achieves multifunctional purification effects in challenging environments through synergistic photocatalysis for continuous sewage purification.
[0003] In recent years, two-dimensional transition metal carbide / nitride (MXene) nanomaterials have attracted extensive interest from researchers due to their special electronic, physical, chemical and mechanical properties. Research reports show that multilayer MXene nanomaterials exhibit excellent photothermal performance due to their superior electromagnetic shielding and localized surface plasmon resonance (LSPR) effect. In addition, as a new type of two-dimensional transition metal carbide / nitride, MXene is also a commonly used coupled photocatalyst material in heterostructure systems. This is due to its unique properties, such as special structural stability, high concentration of hydrophilic functional groups on the surface, superior metallic conductivity, and increased redox properties due to the position of Ti at the surface end. Therefore, MXene has abundant surface functional groups and exposed metal sites, which give it a high adsorption capacity comparable to that of 2D photocatalysts, making it an effective co-catalyst for accelerating the photocatalytic decomposition of organic dyes. At the same time, graphitic carbon nitride (g-C3N4) has been widely used in the photodegradation of organic pollutants due to its graphite-like sp2-bonded CN structure and narrow band gap of 2.7 eV. Based on the previous research reports, we expect that the g-C3N4 photocatalyst can be combined with MXene to further improve its photocatalytic activity. In addition, the excellent metallic conductivity of MXene can generate Schottky junctions in heterostructure systems, thereby generating intrinsic electric fields. This phenomenon significantly enhances the separation and mobility of photogenerated carriers in heterostructure systems, thereby improving the performance of photocatalytic degradation. SiO2 has the advantages of high cost-effectiveness, good hydrophilicity, easy synthesis, and controllable particle size. It is currently one of the most commonly used inorganic nano-modified membrane additives. Ionic liquids are known as environmentally friendly solvents. They are completely composed of ions at room temperature, have extremely low volatility, excellent stability and electrochemical properties. Polyionic liquids are a new type of polymer electrolyte with controllable charge characteristics and wide ionic structural versatility. Ionic liquids have been used to prepare highly hydrophilic membranes and inhibitory materials. By regulating the polymerization of ionic liquids on SiO2 particles, the structure and properties of SiO2 particles can be modified. The properties of the membrane surface can be controlled according to its charge characteristics, thereby improving the salt tolerance of the membrane and inhibiting the agglomeration of SiO2 particles. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing a PC-SP-MCN double-layer Janus composite membrane with synergistic solar-driven interfacial evaporation and photocatalysis, and explores its application in the purification and treatment of high-salinity solutions, wastewater containing dyes, heavy metal ions and biological contamination.
[0005] In order to achieve the above purpose, the technical solutions provided are as follows:
[0006] The invention also provides a method for preparing a PC-SP-MCN double-layer Janus composite film that synergizes solar energy-driven interface evaporation and photocatalysis, comprising the following steps:
[0007] Step 1: Preparation of SiO2-PIL particles, specifically comprising the following steps:
[0008] Step (1), grafting Cl groups onto SiO2 to obtain a SiO2-Cl precursor;
[0009] Step (2), using SiO2-Cl precursor and CuBr2 as catalysts and 2,2'-bipyridine as a ligand, [AMIm]PF6 was immersed in a custom-made three-necked flask filled with DMF;
[0010] Step (3), the obtained mixture was uniformly stirred under a nitrogen atmosphere, 0.05 g of AIBN was added to the DMF solution in a three-necked flask and stirred, and the [AMIm]PF6 cations were grafted onto the SiO2-Cl particles to form a polyelectrolyte brush;
[0011] Step (4), collecting the obtained product by centrifugation, washing it with methanol-water solution and ethanol for several times, and finally drying and collecting the modified SiO2-PIL;
[0012] Step 2: Preparation of MXene / g-C3N4, specifically comprising the following steps:
[0013] Step (1), filling urea powder into an alumina crucible, and then continuously heating it in a heating furnace;
[0014] Step (2), after the reaction is completed, the crucible is cooled to room temperature, the obtained g-C3N4 powder is collected and crushed in a mortar;
[0015] Step (3), adding g-C3N4 to MXene and deionized water, ultrasonically treating at room temperature, heating and stirring until slurry is formed, and drying the sample in an oven overnight and collecting it to obtain MXene / g-C3N4;
[0016] Step 3: Preparation of PC-SP-MCN mixed film, specifically comprising the following steps:
[0017] Step (1), adding MXene / g-C3N4 catalyst to DMF solution and stirring, then adding Tween 80, PVDF, PEG, CB, stirring the obtained solution, and cooling to room temperature to obtain solution A;
[0018] Step (2), adding SiO2-PIL to the DMF solution, mixing the mixture with Tween 80, PVDF, PEG and CaCO3 after ultrasonication, heating the solution and stirring it, and then cooling it to room temperature to obtain solution B;
[0019] Step (3), casting liquid A on a glass plate, casting liquid B on the formed membrane A, and then placing the formed membrane in an acidic aqueous solution, generating a large number of bubbles in the solution. After the process is completed, the double-layer membrane is taken out from the acidic solution and soaked in clean water to remove the remaining acidic residue, so that the membrane becomes neutral, and a PC-SP-MCN mixed membrane is obtained.
[0020] Preferably, in step (2) of step one, the mass ratio of the SiO2-Cl precursor to CuBr2 is 50:1.
[0021] Preferably, in step (2) of step 1, the mass ratio of 2,2'-bipyridine (BPy) to [AMIm]PF6 is 7:1000.
[0022] Preferably, in step three, the mass ratio of PVDF, PEG and CaCO3 is 32:8:1.
[0023] The present invention also provides a PC-SP-MCN double-layer Janus composite film material that cooperates with solar energy to drive interface evaporation and photocatalysis, which is prepared by applying the above method.
[0024] The present invention provides the application of a PC-SP-MCN double-layer Janus composite membrane that cooperates with solar energy to drive interface evaporation and photocatalysis in seawater desalination and in the purification and treatment of wastewater containing dyes, heavy metals and polluted by organisms.
[0025] Preferably, the PC-SP-MCN double-layer Janus composite membrane that synergizes solar energy-driven interfacial evaporation and photocatalysis is placed in different water source environments and directly irradiated with sunlight.
[0026] The beneficial effects of the present invention are as follows: the present invention firstly introduces a preparation method of a PC-SP-MCN double-layer Janus composite membrane with coordinated solar-driven interfacial evaporation and photocatalysis by using graft copolymerization and phase transition as the main synthesis methods. Secondly, its application in seawater desalination and purification of wastewater containing dyes, heavy metals and biological contamination is introduced. In addition, the present invention prepares a double-layer Janus composite membrane by phase transition, and the introduced silica grafted ionic liquid makes the material have good salt resistance. The excellent light absorption, salt resistance and anti-biological contamination properties enable it to show efficient solar-driven interfacial evaporation efficiency and photocatalytic ability. Through application research in seawater desalination and purification of wastewater containing dyes, heavy metals and biological contamination, it is preliminarily believed that the PC-SP-MCN double-layer Janus composite membrane with coordinated solar-driven interfacial evaporation and photocatalysis prepared in the present invention has high solar energy conversion efficiency, excellent salt resistance and anti-fouling properties and good photocatalytic ability, and can find wide application in the fields of seawater desalination and wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a diagram of the preparation of the PC-SP-MCN double-layer Janus composite film of the present invention that synergizes solar energy-driven interfacial evaporation and photocatalysis.
[0028] Figure 2 In the figure, a, b, c are optical photographs and SEM images of the upper layer of PC-SP-MCN; d is the water contact angle; e, f, g are optical photographs and SEM images of the lower layer of PC-SP-MCN; h is the water contact angle; i, j are EDS element mappings of the upper and lower layers of PC-SP-MCN.
[0029] Figure 3 In the figure, a and b are infrared spectra of PVDF, SiO2, SiO2-PIL, and PM-SiO2-PIL; c is the potential diagram of SiO2 and SiO2-PIL; d is the thermogravimetric curve of SiO2 and SiO2-PIL; e and f are BET spectra of SiO2 and SiO2-PIL.
[0030] Figure 4 a and b are pure water and PC-SP-MCN composite Janus membrane at 1 kW m -2 Mass loss and evaporation efficiency of the upper and lower surfaces under solar irradiation; c is the mass loss and evaporation efficiency of PC-SP-MCN at 1-3 kW m -2 Infrared camera images of surface temperature changes under sunlight; d and e are images of PC-SP-MCN at 1 to 3 kW m -2 Mass loss and evaporation efficiency and rate under solar irradiation; f is the cycle curve of PC-SP-MCN under solar irradiation within this range; g is a schematic diagram of the device for using PC-SP-MCN composite Janus membrane for SDIE experiment.
[0031] Figure 5 In the figure, a is the mass loss of PC-SP-MCN in simulated seawater and salt solutions of different concentrations; b is the evaporation efficiency and rate of PC-SP-MCN in simulated seawater and salt solutions of different concentrations; c, d are the mass loss and evaporation rate of PC-SP-MCN after continuous evaporation for 8 h in a 20% NaCl solution; e, f are the concentrations of metal ions in seawater before and after evaporation; g is a schematic diagram of the potential salt-tolerance mechanism of PC-SP-MCN.
[0032] Figure 6 In the figure, a and c are the UV-visible spectra of MB, MO and RhB at different time intervals; d is the photocatalytic curve of PC-SP-MCN for different dyes such as MB, MO, RhB, etc.; e is the kinetic fitting of the pseudo-first-order reaction model of MB, MO and RhB on PC-SP-MCN; f is the comparative analysis of the photocatalytic efficiency of MB, MO and RhB with or without adding PC-SP-MCN; g is the degradation curve of PC-SP-MCN after 5 cyclic photodegradation, taking MB as an example; h and I are the antibacterial zone test photos of PC-SP-MCN against Escherichia coli and Staphylococcus aureus. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The method for preparing the PC-SP-MCN double-layer Janus composite film of the present invention by synergistic solar energy driven interface evaporation and photocatalysis comprises the following steps:
[0035] (1) Preparation of SiO2-PIL particles
[0036] SiO2 was first grafted with Cl groups (SiO2-Cl) and then used as a precursor to synthesize SiO2-PIL. 10g of vacuum-dried SiO2 and 6mL of 3-chloropropyl-triethoxysilane (ClTES) were added to 250mL of DMF, heated at 80℃ and stirred continuously for 12h. The resulting product was collected by centrifugation, washed with ethanol several times, and then dried at 50℃ in vacuum for 24h. Then SiO2-PIL particles were synthesized using atom transfer radical polymerization (ATRP) method with 5.0g of SiO2-Cl precursor and 0.1g of CuBr2 as catalyst. 20.0g of [AMIm]PF6 was immersed in a custom-made three-necked flask filled with 200mL of DMF with 0.14g of 2,2′-bipyridine (BPy) as ligand. The resulting mixture was stirred evenly for 10min under nitrogen atmosphere. A 10 g / L AIBN solution was added to the flask and stirred in 10 mL DMF for 48 h to graft [AMIm]PF6 cations onto SiO2-Cl particles at 70 °C to form polyelectrolyte brushes. The resulting product was collected by centrifugation and washed several times with methanol-water solution and ethanol. Finally, the modified SiO2-PIL was dried in vacuum at 50 °C for 24 h.
[0037] Among them, Cl groups were grafted on the surface of SiO2, which was then used as a precursor to synthesize SiO2-PIL. The purpose was to graft ionic liquids on the surface of SiO2 by atom transfer radical polymerization.
[0038] (2) Preparation of MXene / g-C3N4
[0039] g-C3N4 was synthesized by urea thermal condensation method. Urea powder was filled in an alumina crucible and then continuously heated in a 500°C furnace at a heating rate of 5°C / min for 120 min. After the reaction was completed, the crucible was cooled to room temperature, and the powder in the crucible was collected and crushed in a mortar. MXene / g-C3N4 heterostructure photocatalyst composite material was prepared by wet impregnation method. First, 1g-C3N4 was added to 0.01g MXene and 30mL deionized water. Ultrasonic treatment was performed at room temperature for 30min, and heated and stirred for 45min until slurry was formed. The sample was dried in an oven at 60°C overnight and collected.
[0040] Among them, the purpose of preparing MXene / g-C3N4 heterojunction is to prepare PC-SP-MCN film with good photocatalytic performance.
[0041] (3) Preparation of PC-SP-MCN mixed membrane
[0042] First, 0.015g of MXene / g-C3N4 catalyst was added to 8mL DMF solution and stirred for 30min, and then 1mL Tween 80, 1.6g PVDF, 0.4g PEG, and 0.05g CB were added. The resulting solution was heated to 80°C and stirred for 1h. After cooling to room temperature, it was further stirred for 24h to obtain solution A. Then, 0.05g SiO2-PIL was added to 8mL DMF solution, ultrasonicated for 30min, and then the mixture was mixed with 1ml Tween 80, 1.6g PVDF, 0.4g PEG, and 0.05g CaCO3, and the solution was heated to 80°C, stirred for 1h, cooled to room temperature again, and stirred for 24h to obtain solution B. The next step is to cast the membrane-forming liquid on a glass plate; the membrane-forming liquid B is cast on top of the membrane-forming liquid A, and then the formed membrane is placed in an acidic aqueous solution in which a large number of bubbles are generated; after the process is completed, the double-layer membrane is removed from the acidic solution and soaked in clean water for 48 hours to remove any remaining acidic residues and make the membrane neutral. This process ensures that the film does not contain any unwanted chemicals and is ready to be used in its intended application.
[0043] The formed membrane is placed in an acidic aqueous solution in order to modify it with CaCO3 so that its surface has a large number of pores and thus has excellent hydrophilicity.
[0044] Example 1 Preparation of SiO2-PIL particles
[0045] SiO2 was first grafted with Cl groups (SiO2-Cl) and then used as a precursor to synthesize SiO2-PIL. 10g of vacuum-dried SiO2 and 6mL of 3-chloropropyl-triethoxysilane (ClTES) were added to 250mL of DMF, heated at 80℃ and stirred continuously for 12h. The resulting product was collected by centrifugation, washed with ethanol several times, and then vacuum dried at 50℃ for 24h. Then SiO2-PIL particles were synthesized using atom transfer radical polymerization (ATRP) method with 5.0g of SiO2-Cl precursor and 0.1g of CuBr2 as catalyst. 20.0g of [AMIm]PF6 was immersed in a three-necked flask filled with 200mL of DMF with 0.14g of 2,2′-bipyridine (BPy) as ligand. The resulting mixture was stirred evenly for 10min under nitrogen atmosphere. A 10 g / L AIBN solution was added to the flask and stirred in 10 mL DMF for 48 h to graft [AMIm]PF6 cations onto SiO2-Cl particles at 70 ° C to form polyelectrolyte brushes. The resulting product was collected by centrifugation and washed several times with methanol-water solution and ethanol.
[0046] Figure 1This is a diagram of the preparation of the PC-SP-MCN double-layer Janus composite film of the present invention that synergizes solar energy-driven interfacial evaporation and photocatalysis.
[0047] like Figure 1 As shown, a new type of Janus composite membrane with strong salt resistance and anti-biological fouling performance was proposed in this study. PVDF was used as the membrane material, SiO2-PIL was used as the hydrophilic agent, calcium carbonate (CaCO3) and hydrochloric acid (HCl) were used as pore-forming agents for hydrophilic modification, and MXene / g-C3N4 was used as the photocatalyst to prepare a composite polyvinylidene fluoride (PVDF) Janus membrane (PC-SP-MCN) with Schottky junction.
[0048] Example 2 PC-SP-MCN double-layer Janus composite membrane
[0049] (1) Preparation of MXene / g-C3N4:
[0050] g-C3N4 was synthesized by urea thermal condensation method. Urea powder was filled in an alumina crucible and then continuously heated in a 500°C furnace at a heating rate of 5°C / min for 120 min. After the reaction was completed, the crucible was cooled to room temperature, and the powder in the crucible was collected and crushed in a mortar. MXene / g-C3N4 heterostructure photocatalyst composite material was prepared by wet impregnation method. First, 1g-C3N4 was added to 0.01g MXene and 30mL deionized water. Ultrasonic treatment was performed at room temperature for 30min, and heated and stirred for 45min until slurry was formed. The sample was dried in an oven at 60°C overnight and collected.
[0051] (2) Preparation of PC-SP-MCN mixed membrane:
[0052] First, 0.015g of MXene / g-C3N4 catalyst was added to 8mL DMF solution and stirred for 30min, and then 1mL Tween 80, 1.6g PVDF, 0.4g PEG, and 0.05g CB were added. The resulting solution was heated to 80°C and stirred for 1h. After cooling to room temperature, it was further stirred for 24h to obtain solution A. Then, 0.05g SiO2-PIL was added to 8mL DMF solution, ultrasonicated for 30min, and then the mixture was mixed with 1ml Tween 80, 1.6g PVDF, 0.4g PEG, and 0.05g CaCO3, and the solution was heated to 80°C, stirred for 1h, cooled to room temperature again, and stirred for 24h to obtain solution B. The next step is to cast the membrane-forming liquid on a glass plate; the membrane-forming liquid B is cast on top of the membrane-forming liquid A, and then the formed membrane is placed in an acidic aqueous solution in which a large number of bubbles are generated; after the process is completed, the double-layer membrane is removed from the acidic solution and soaked in clean water for 48 hours to remove any remaining acidic residues and make the membrane neutral. This process ensures that the film does not contain any unwanted chemicals and is ready to be used in its intended application.
[0053] Figure 2 In the figure, a, b, c are optical photographs and SEM images of the upper layer of PC-SP-MCN; d is the water contact angle; e, f, g are optical photographs and SEM images of the lower layer of PC-SP-MCN; h is the water contact angle; i, j are EDS element mappings of the upper and lower layers of PC-SP-MCN.
[0054] like Figure 2 The optical photographs of ah clearly show the different colors of the upper and lower layers, which can be attributed to the presence of carbon black in the upper layer. Due to the addition of CaCO3, the lower PVDF membrane presents a uniform pore structure, and the introduction of SiO2-PIL not only does not block the pores, but enhances the hydrophilicity. On the other hand, the upper membrane has no obvious pores and has obvious MXene / g-C3N4 particles on the surface, which can effectively store heat and has a hydrophobicity of 80°. The lower membrane has good hydrophilicity and a contact angle of 0°, which is conducive to the rapid transfer of water to the middle layer.
[0055] Figure 3 In the figure, a and b are infrared spectra of PVDF, SiO2, SiO2-PIL and PM-SiO2-PIL; c is the potential diagram of SiO2 and SiO2-PIL; d is the thermogravimetric curve of SiO2 and SiO2-PIL; e and f are BET spectra of SiO2 and SiO2-PIL.
[0056] like Figure 3As shown in ab, the pore size distribution of SiO2-PILs / starch was tested by mercury intrusion (MIP). From the mercury intrusion / extrusion mercury intrusion curve, it can be seen that when the pore size is 50-350μm, the intrusion of mercury tends to be flat, and when the pore size is less than 50μm, the intrusion of mercury increases rapidly, the porosity is 60.57%, and the total pore area is 0.195m 2 g -1 , indicating that SiO2-PILs / starch has rich macroporous structure. Figure 3 e, f: The average pore size of SiO2 is 0.82 nm, and the average pore size of SiO2-PIL is 0.68 nm. Figure 3 c shows the charge properties of primary SiO2, SiO2-Cl, and SiO2-PIL. Figure 3 d is the composition of the prepared particles characterized by TGA.
[0057] Example 3 Application of the PC-SP-MCN double-layer Janus composite membrane with synergistic solar-driven interfacial evaporation and photocatalysis of the present invention in seawater desalination and purification of wastewater containing dyes, heavy metals and biological contamination.
[0058] The PC-SP-MCN double-layer Janus composite film prepared in Example 2 was used as an interfacial evaporation system. The local temperature of the PC-SP-MCN surface at different time points during the interfacial evaporation process was measured by an infrared camera for real-time observation and recording. The electronic balance monitored and recorded the real-time mass of water during the evaporation process. The evaporation rate of PC-SP-MCN was obtained according to the slope of the curve of the water mass changing with time, and the corresponding photothermal conversion efficiency was obtained by calculation. In addition, at 1 kW m -2 The PC-SP-MCN was tested for 10 cycles of evaporation efficiency under different light intensity. The wastewater was prepared by using a solution containing 15 mg / L methylene blue (MB), rhodamine B (RhB) and methyl orange (MB) as a simulated organic dye wastewater. -2 (equivalent to 100mW cm -2 ) photocatalytic intensity, the photocatalytic degradation performance of single dye and PC-SP-MCN was tested.
[0059] Figure 4 a, b are pure water and PC-SP-MCN composite Janus membrane at 1 kW m -2 Mass loss and evaporation efficiency of the upper and lower surfaces under solar irradiation; c is the mass loss and evaporation efficiency of PC-SP-MCN at 1-3 kW m -2 Infrared camera images of surface temperature changes under sunlight; d and e are images of PC-SP-MCN at 1 to 3 kW m -2Mass loss and evaporation efficiency and rate under solar irradiation; f is the cycle curve of PC-SP-MCN under solar irradiation within this range; g is a schematic diagram of the device for using PC-SP-MCN composite Janus membrane for SDIE experiment.
[0060] like Figure 4 As shown in Figure 1, experiments were conducted to evaluate the evaporation performance of pure water, PC-SP-MCN, and their respective positive and negative sides under SDIE. -2 When exposed to solar irradiation, the mass loss of PC-SP-MCN was significantly higher than that of the control material, indicating that it has superior evaporation ability. In order to further study the evaporation efficiency and rate of PC-SP-MCN, the correlation between the mass and time of various materials was comprehensively analyzed. Figure 4 As shown in b, the evaporation efficiency of PC-SP-MCN is 1.51 kg m -2 h -1 , the evaporation rate is 91%. Figure 4 ce is the change of surface temperature, mass loss, evaporation efficiency and rate of PC-SP-MCN under different light intensities. -2 The evaporation efficiency of PC-SP-MCN was 91%, 70% and 64% under different light intensities. The increased light intensity resulted in higher heat loss, which led to a decrease in evaporation efficiency. In order to gain a deeper understanding of the surface temperature changes of PC-SP-MCN, a significant increase in the surface temperature of the material was observed using an infrared thermal imager. When the solar irradiation intensity was between 1 and 3 kW m -2 In the range of 2.5 ℃ and 4.5 ℃, the surface temperature of PC-SP-MCN increased from about 18.0℃ to 40.5℃, 47.7℃ and 53.8℃ respectively. -2 ) showed that PC-SP-MCN experienced 5 cycles, indicating its stable evaporation ability, indicating that the composite Janus membrane has good cyclic stability. Figure 4 g: Experimental setup for SDIE experiment using PC-SP-MCN composite Janus membrane.
[0061] Figure 5 a is the mass loss of PC-SP-MCN in simulated seawater and salt solutions of different concentrations; b is the evaporation efficiency and rate of PC-SP-MCN in simulated seawater and salt solutions of different concentrations; c, d are the mass loss and evaporation rate of PC-SP-MCN after continuous evaporation for 8 h in 20% NaCl solution; e, f are the concentrations of metal ions in seawater before and after evaporation; g is a schematic diagram of the potential salt-tolerance mechanism of PC-SP-MCN.
[0062] like Figure 5 As shown in a and b, when the solar irradiance is 1kW m -2Under the condition of high salt concentration in the solution, the stability of PC-SP-MCN was not significantly affected, indicating that PC-SP-MCN had excellent salt resistance after doping with SiO2-PIL. Figure 5 c, d show that when the NaCl concentration is 20 wt%, the evaporation efficiency of PC-SP-MCN is 83% and the evaporation rate is 1.39 kg m -2 h -1 . Figure 5 c, d are salt tolerance tests of PC-SP-MCN immersed in 20% NaCl solution for 8 hours. Figure 5 As shown in (cd), the evaporation rate of PC-SP-MCN remains stable under a solar irradiance of 1 kWm-2. Figure 5 ef is the various ions (Na + Mg 2+ , K + , Cu 2+ , Pb 2+ and Zn 2+ ) levels were significantly reduced, indicating that PC-SP-MCN had a high retention rate for ions.
[0063] Figure 6 In the figure, a and c are the UV-visible spectra of MB, MO and RhB at different time intervals; d is the photocatalytic curve of PC-SP-MCN for different dyes such as MB, MO, RhB, etc.; e is the kinetic fitting of the pseudo-first-order reaction model of MB, MO and RhB on PC-SP-MCN; f is the comparative analysis of the photocatalytic efficiency of MB, MO and RhB with or without adding PC-SP-MCN; g is the degradation curve of PC-SP-MCN after 5 cyclic photodegradation, taking MB as an example; h and I are the antibacterial zone test photos of PC-SP-MCN against Escherichia coli and Staphylococcus aureus.
[0064] like Figure 6 As shown in the figure, as the photocatalytic reaction proceeds, the characteristic peaks of the UV-visible absorption spectra of MB, RhB and MO solutions gradually decrease, indicating that PC-SP-MCN has excellent photocatalytic ability for organic pollutants. Figure 6 As shown in d and f, the degradation rates of MB, RhB and MO decreased from the initial value of 1 to about 0.0494, 0.0340 and 0.2577. The removal rates of MB, RhB and MO by PC-SP-MCN composites were 95.06%, 96.9% and 74.23%, respectively. Figure 6 The kinetic curve shown in e was used to calculate the kinetic parameters of the reaction, and the reaction conformed to the first-order kinetic model. Figure 6g shows a cyclic photocatalytic degradation experiment using PC-SP-MCN as a MB degradation catalyst. The results show that PC-SP-MCN has consistent photocatalytic activity even after five consecutive cycles, highlighting its excellent reusability. Figure 5 The widths of the inhibition zones for h were approximately 3.5 mm and 4.2 mm, respectively, which further confirmed the effective antibacterial properties of the composite membrane.
[0065] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. The preparation method of PC-SP-MCN double-layer Janus composite film driven by solar energy interface evaporation and photocatalysis is as follows: Step 1: Preparation of SiO2-PIL particles, specifically comprising the following steps: Step (1), grafting Cl groups onto SiO2 to obtain a SiO2-Cl precursor; Step (2), using SiO2-Cl precursor and CuBr2 as catalysts and 2,2'-bipyridine as a ligand, [AMIm]PF6 was immersed in a custom-made three-necked flask filled with DMF; Step (3), the obtained mixture was uniformly stirred under a nitrogen atmosphere, 0.05 g of AIBN was added to the DMF solution in a three-necked flask and stirred, and the [AMIm]PF6 cations were grafted onto the SiO2-Cl particles to form a polyelectrolyte brush; Step (4), collecting the obtained product by centrifugation, washing it with methanol-water solution and ethanol for several times, and finally drying and collecting the modified SiO2-PIL; Step 2: Preparation of MXene / g-C3N4, specifically comprising the following steps: Step (1), filling urea powder into an alumina crucible, and then continuously heating it in a heating furnace; Step (2), after the reaction is completed, the crucible is cooled to room temperature, the obtained g-C3N4 powder is collected and crushed in a mortar; Step (3), adding g-C3N4 to MXene and deionized water, ultrasonically treating at room temperature, heating and stirring until slurry is formed, and drying the sample in an oven overnight and collecting it to obtain MXene / g-C3N4; Step 3: Preparation of PC-SP-MCN mixed film, specifically comprising the following steps: Step (1), adding MXene / g-C3N4 catalyst to DMF solution and stirring, then adding Tween 80, PVDF, PEG, CB, stirring the obtained solution, and cooling to room temperature to obtain solution A; Step (2), adding SiO2-PIL to the DMF solution, mixing the mixture with Tween 80, PVDF, PEG and CaCO3 after ultrasonication, heating the solution and stirring it, and then cooling it to room temperature to obtain solution B; Step (3), casting liquid A on a glass plate, casting liquid B on the formed membrane A, and then placing the formed membrane in an acidic aqueous solution, generating a large number of bubbles in the solution. After the process is completed, the double-layer membrane is taken out from the acidic solution and soaked in clean water to remove the remaining acidic residue, so that the membrane becomes neutral, and a PC-SP-MCN mixed membrane is obtained.
2. The method for preparing the PC-SP-MCN double-layer Janus composite film with synergistic solar-driven interfacial evaporation and photocatalysis according to claim 1, characterized in that: In step (2) of step one, the mass ratio of the SiO2-Cl precursor to CuBr2 is 50:
1.
3. The method for preparing the PC-SP-MCN double-layer Janus composite film with synergistic solar-driven interfacial evaporation and photocatalysis according to claim 1, characterized in that: In step (2) of step one, the mass ratio of 2,2-bipyridine (BPy) and [AMIm]PF6 is 7:1000.
4. The method for preparing the PC-SP-MCN double-layer Janus composite film with synergistic solar-driven interfacial evaporation and photocatalysis according to claim 1, characterized in that: In step three, the mass ratio of PVDF, PEG and CaCO3 is 32:8:
1.
5. A PC-SP-MCN double-layer Janus composite film prepared according to any one of the preparation methods of claims 1 to 4 that synergizes solar energy driven interfacial evaporation and photocatalysis.
6. Application of the PC-SP-MCN double-layer Janus composite membrane with synergistic solar-driven interfacial evaporation and photocatalysis as described in claim 5 in seawater desalination and in the purification of wastewater containing dyes, heavy metals and biological pollution.
7. The use according to claim 6, characterized in that: The PC-SP-MCN double-layer Janus composite film with synergistic solar-driven interfacial evaporation and photocatalysis was placed in different water source environments and directly exposed to sunlight.
Citation Information
Patent Citations
Preparation method of optically-driven self-cleaning Ti3C2-TiO2-C3N4 heterojunction separation membrane
CN114452826A
Super-hydrophilic photocatalytic self-cleaning ceramic composite membrane as well as preparation method and application thereof
CN116850796A